2013
DOI: 10.1016/j.antiviral.2013.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Multiple heterologous M2 extracellular domains presented on virus-like particles confer broader and stronger M2 immunity than live influenza A virus infection

Abstract: The influenza M2 ectodomain (M2e) is poorly immunogenic and has some amino acid changes among isolates from different host species. We expressed a tandem repeat construct of heterologous M2e sequences (M2e5x) derived from human, swine, and avian origin influenza A viruses on virus-like particles (M2e5x VLPs) in a membrane-anchored form. Immunization of mice with M2e5x VLPs induced protective antibodies cross-reactive to antigenically different influenza A viruses and conferred cross protection. Anti-M2e antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 40 publications
0
75
0
1
Order By: Relevance
“…A possible mechanism by which M2 antibodies provide protection is that influenza viruses bound to non-neutralizing antibodies are likely to be recognized and removed by opsonophagocytosis via Fc receptors [12, 2327]. In this study, M2e specific antibody after M2e5x VLP immunization was reactive to M2-expressing MDCK cell or MDCK cells infected with influenza viruses, which suggests that binding antibody to infected cell can mediate opsonophagocytosis.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…A possible mechanism by which M2 antibodies provide protection is that influenza viruses bound to non-neutralizing antibodies are likely to be recognized and removed by opsonophagocytosis via Fc receptors [12, 2327]. In this study, M2e specific antibody after M2e5x VLP immunization was reactive to M2-expressing MDCK cell or MDCK cells infected with influenza viruses, which suggests that binding antibody to infected cell can mediate opsonophagocytosis.…”
Section: Discussionmentioning
confidence: 57%
“…In our previous studies, M2e5x VLP was shown to confer effective cross protection against H1, H3, and H5 subtype influenza viruses [1112]. Here, we investigated whether immunization with M2e5x VLPs would improve the efficacy of cross-protection against influenza A viruses in the presence of pre-existing vaccine immunity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with previous studies reporting that M2e conjugate protein vaccines with adjuvants were shown to confer survival protection but not effective in preventing weight loss (40-42). Encouragingly, M2e5x VLP vaccination in the absence of adjuvants was effective in preventing weight loss as well as broadening cross protection against H1, H3, and H5 subtype IAVs (22, 43). Thus, as shown herein, it is highly significant that a universal vaccination strategy can provide superior cross protection to current vaccines in the scenario of when a first infecting virus is antigenically different from a vaccine strain.…”
Section: Discussionmentioning
confidence: 99%
“…At day 7, lung samples were collected from three mice of each group to titer viruses. Lung extracts were prepared and the viral titers were determined (Kim et al, 2013a). …”
Section: Methodsmentioning
confidence: 99%